PENDIDIKAN KESEHATAN JIWA TENTANG DEPRESI PADA MASYARAKAT WILAYAH PUSKESMAS KARANG ASAM SAMARINDA - Dwi Astri Andriani; Milkhatun; Nur Ariska Meritama Meritama; Faramita Kumala Sari; Friska Meirina Andriani (Open Edutech Indonesia, 2024)
Abstract. Depressive disorder or depression is a common mental health condition and can be experienced by anyone. This condition is characterized by a low mood or loss of pleasure or interest in a particular activity over a long period of time. Depression is different from the usual mood swings and everyday feelings. Objective: To provide knowledge and understanding of early detection of depression in people in the working area of the Karang Asam Samarinda Health Center. The method used in this Health Education is the lecture method and filling out pre and post tests using the Dass 21 questionnaire and discussions using leaflet media containing materials about depression. This Health Education activity was attended by 15 respondents who visited the Karang Asam Samarinda Health Center. The results obtained from the counseling pre-test showed that several respondents experienced very severe depressive disorder (13.3%), severe depressive disorder (20%), and moderate depressive disorder (66,7 %).With an average of 3.47 and post-test counseling, several respondents were found with severe depressive disorder (13.3%), moderate depressive disorder (66.7%) and mild depressive disorder (20%). Conclusion This Health Education activity provides the benefit of increasing understanding in the early detection of risks and symptoms as well as the prevention of depression